(untitled) (Research, Society and Development, 2022)
The teaching of ecology, behavior and animal domestication is still a challenge for education professionals, especially in relation to interspecific interactions between humans and animals. Because it is a very theoretical content and students end up viewing it as boring and dull. One way to solve this problem is through the use of playful teaching materials that facilitate students’ understanding and interaction with the content. However, teaching resources on the subject are still scarce or expensive. With this, this work aims to develop a playful multidisciplinary discursive text as a low-cost didactic resource in the teaching of ecology and animal behavior. For this, a playful text was created in the form of a chronicle that can be used in elementary, secondary and higher education, based on books on animal behavior, general biology, ecology and anthropology, which entertains the reader with a comic and interactive narrative. The text tells the story of a mouse and the frustrated attempts of one of the characters to eliminate it from his house, secretly describing an anthropized food web and the harmonic and disharmonious interspecific relationships of commensalism, predation, cooperation, mutualism and competition of the animals. Characters, in addition to their variations according to their behavior. The didactic resource produced proves to be a good teaching tool, as it provides an interactive and fun way to learn the content, in addition to acting as a facilitator of dialogue between the teacher and the student.